2003
DOI: 10.1007/s10096-003-0988-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Borrelia burgdorferi sensu lato, Anaplasma and Ehrlichia Species, and Spotted Fever Group Rickettsiae in Ticks from Southeastern Europe

Abstract: Prevalence data for tick-borne pathogens are used to assess the risk for human health. In this study the presence and identity of Borrelia burgdorferi sensu lato, Ehrlichia, Anaplasma, and Rickettsia species in Bulgarian Ixodes ricinus ticks and in non- Ixodes ticks from Turkey and Albania was determined by polymerase chain reaction (PCR) and reverse line blot hybridization. In the adult Bulgarian ticks, the prevalence of Borrelia burgdorferi sensu lato infection was approximately 40%, while Borrelia afzelii w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 53 publications
5
76
2
1
Order By: Relevance
“…As described in this study, the overall Bb seroprevalence was only 0.6% and there was not a statistical association between Bb and Ap seroreactivity among the three study sites. No studies have reported Ap in R. sanguineus ticks; however, a recent study reported Ap DNA in R. bursa from Albania [4]. Dog sera from Mallorca recognized Ec antigens by IFA testing (17.6%) that were not detected by a commercial diagnostic test (Snap 3DX) that uses Ec synthetic peptides as antigens (0%) [2].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As described in this study, the overall Bb seroprevalence was only 0.6% and there was not a statistical association between Bb and Ap seroreactivity among the three study sites. No studies have reported Ap in R. sanguineus ticks; however, a recent study reported Ap DNA in R. bursa from Albania [4]. Dog sera from Mallorca recognized Ec antigens by IFA testing (17.6%) that were not detected by a commercial diagnostic test (Snap 3DX) that uses Ec synthetic peptides as antigens (0%) [2].…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that Ap is transmitted by Ixodes ricinus ticks, which also transmit Bb in central European countries such as in central Italy [5], Bulgaria [4] and Switzerland [29]. In northern Spain (regions close to the atlantic ocean), there are reports of Ap infection in Ixodes ticks, in humans [27], in larvae of Neotrombicula autumnalis [10], in sheep where infection can result in abortions [12], in cattle with non-specific illness [20] and in wild small mammals and roe deer [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, it has been detected by PCR in ticks in several European countries, mainly in southern and southeastern Europe: Spain, Italy, Portugal, Slovakia, Albania, Hungary, Bulgaria, Moldova, Eastern Ukraine and Switzerland (Marquez et al, 1998;Sekeyova et al, 2000;Beninati et al, 2002;Dobler & Wolfel, 2009;Sreter-Lancz et al, 2006;de Carvalho et al, 2008;Boretti et al, 2009;Movila et al, 2009). The prevalence of R. monacensis infection in I. ricinus ticks collected in nature varied between 2.4 % in Spain, 8.6 % in Germany, 12.2 % in Slovakia and 52.9 % in Bulgaria (Christova et al, 2003;Sekeyova et al, 2000). Recently, in two patients from Spain, R. monacensis was detected in blood samples by molecular tools and one rickettsial strain was isolated by shell vial culture.…”
Section: Rickettsia Monacensismentioning
confidence: 99%
“…It was first isolated from I. ricinus in Switzerland in 1979 . R. helvetica has been detected in I. ricinus in many European countries, including France, Spain, Portugal, Austria, Denmark, the Netherlands, Switzerland, Sweden, Portugal, Germany, Bulgaria, Slovenia, Poland, Hungary, Moldova, Eastern Ukraine and Italy (Nijhof et al, 2007;Christova et al, 2003;Dobler & Wolfel, 2009;Marquez, 2008;Parola et al, 2005;Nilsson et al, 1999;Movila et al, 2009). In Sweden, two patients with clinical symptoms of fatal perimyocarditis were infected with R. helvetica, as confirmed by electron microscopy, PCR and serology (Nilsson et al, 1999).…”
Section: Rickettsia Helveticamentioning
confidence: 99%